2021
DOI: 10.1002/kpm.1691
|View full text |Cite
|
Sign up to set email alerts
|

Organizational identification and knowledge sharing behavior: Mediating role of organizational citizenship behavior and moderating role of collectivism and leader–member exchange

Abstract: This study aims at testing an empirical model that investigates the relationship between organizational identification (OI) and knowledge sharing behavior (KSB). Drawing on social identity theory and social exchange theory, this study examines the mediating role of organizational citizenship behavior (OCB) in the relationship between OI and KSB. We also examined how collectivism and leader–member exchange (LMX) moderated the OI and KSB relationship. Data of the study consisted of self‐reported responses of emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…Moreover, our research also challenges the mature idea in HRM-OCB literature that the compatibility between employees’ personalities and organizational values, namely organizational identification can enhance OCB ( Fu et al, 2014 ; Shen et al, 2018 ; Zulfiqar and Khan, 2021 ). By drawing on a China-specific management context, we contend that under certain conditions, identification with organizational values may not explain the emergence or enhancement of OCB.…”
Section: Discussionmentioning
confidence: 66%
“…Moreover, our research also challenges the mature idea in HRM-OCB literature that the compatibility between employees’ personalities and organizational values, namely organizational identification can enhance OCB ( Fu et al, 2014 ; Shen et al, 2018 ; Zulfiqar and Khan, 2021 ). By drawing on a China-specific management context, we contend that under certain conditions, identification with organizational values may not explain the emergence or enhancement of OCB.…”
Section: Discussionmentioning
confidence: 66%
“…The findings suggest that STEM learning communities must prioritise "interactive" and "diverse" learning and knowledge sharing to succeed with CSCL. "Interactivity" or connectivity first relates to whether knowledge is the result of member interaction or simply the aggregate of members' opinions [25]. In networked learning environments, students use technology to find and build relationships between resources and ask questions [26].…”
Section: Resultsmentioning
confidence: 99%
“…In networked learning environments, students use technology to find and build relationships between resources and ask questions [26]. Next, "diversity" of members, opinions, and solutions to learn new facts and knowledge by connecting kids to classmates and teachers both inside and outside the classroom [25]. This includes fostering and promoting a diversity of perspectives and ways to problem-solving in which students from varied cultural, social, and ethnic backgrounds can collaborate to achieve a similar goal, such as by considering their peers' ideas and priorities when producing solutions [26].…”
Section: Resultsmentioning
confidence: 99%
“…Liu et al (2021) found that identification with an entity, as implemented via TL, encourages workers to make advantage of their freedom. Also, researchers Zulfiqar and Khan (2021) discovered a strong correlation between organizational identity and knowledge sharing behavior, whereas the moderating effect of collectivism was shown to be minor in this connection. Employee flexibility and work design are successfully increased under transformational leadership.…”
Section: Literature Reviewmentioning
confidence: 99%